Description of Leader Kids: Study of children aged 5-6 years in Kindergarten - Wanda Yulkaryani; Wahyuni Ulpi; Hikrawati Hikrawati (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
This study analysed the description of Leader kids. The formulation of the problem in this study is how to develop the soul of a leader in early childhood. This study aims to describe the soul of leader kids from an early age so that children can become leaders for themselves and others in the future. The method used is a qualitative type with a phenomenological approach. With observation data collection techniques, interviews and documentation. While the validity of the data using triangulation. The research subjects were three children with 7-grade teacher informants with the following criteria: 1) Aged six years and over, 2) Male sex, 3) Have complete parents. In the research results of informants, 57 % say that the spirit of leadership appears before entering school so that it does not entirely affect school activities. In comparison, informants 43 % stated that the soul of the leader kids appeared when they entered school.